PENERAPAN METODE JIGSAW LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DI KELAS V SD NEGERI 18 PEKANBARU - Budiman, Budiman (Jurnal Pendidikan Guru, 2017)
This study aims to determine the application of jigsaw learning method can improve learning achievement subjects Islamic Religious Education students of class V SD Negeri 18 Pekanbaru. This research was conducted at SD Negeri 18 Kota Pekanbaru. The subject of this research is the students of class V SD Negeri 18 Pekanbaru. Grade V students of SD Negeri 18 Pekanbaru consist of 33 students consisting of 15 male students and 18 female students. Technique used to collect data in this research is test, Observation / observation and documentation. This research was conducted by applying jigsaw learning method which has been done for three cycles, it can be concluded that the learning by applying the jigsaw learning method has a positive impact in improving student achievement with the average value of 78.12 in the first cycle, to 81.79 on the cycle II and increased again to 86.88 in cycle III. The success of the learning process is marked by the improvement of students learning mastery in every cycle, that is cycle I (51,52%), cycle II (60,61%) cycle III (84,85%). The conclusion that the application of jigsaw learning method improves learning achievement subjects Islamic Religious Education grade V students SD Negeri 18 Pekanbaru.